2008
DOI: 10.1038/ng.225
|View full text |Cite
|
Sign up to set email alerts
|

MYO5B mutations cause microvillus inclusion disease and disrupt epithelial cell polarity

Abstract: Following homozygosity mapping in a single kindred, we identified nonsense and missense mutations in MYO5B, encoding type Vb myosin motor protein, in individuals with microvillus inclusion disease (MVID). MVID is characterized by lack of microvilli on the surface of enterocytes and occurrence of intracellular vacuolar structures containing microvilli. In addition, mislocalization of transferrin receptor in MVID enterocytes suggests that MYO5B deficiency causes defective trafficking of apical and basolateral pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
325
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 322 publications
(340 citation statements)
references
References 15 publications
11
325
1
3
Order By: Relevance
“…The MYO5B coding region and splice sites (GenBank reference sequence NM_001080467.1) were PCR-amplified and directly sequenced in all patient samples as described previously [Muller et al, 2008]. The sequencing reactions were analyzed on an ABI 3100 DNA sequencer, with BigDye terminator mix (Applied Biosystems, Vienna, Austria).…”
Section: Mutation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The MYO5B coding region and splice sites (GenBank reference sequence NM_001080467.1) were PCR-amplified and directly sequenced in all patient samples as described previously [Muller et al, 2008]. The sequencing reactions were analyzed on an ABI 3100 DNA sequencer, with BigDye terminator mix (Applied Biosystems, Vienna, Austria).…”
Section: Mutation Analysismentioning
confidence: 99%
“…Recently, we have shown that mutations in MYO5B (MIM] 606540), encoding the unconventional type Vb myosin motor protein, are associated with MVID in a first small cohort of patients with earlyonset MVID, firmly establishing autosomal recessive inheritance of MVID [Muller et al, 2008]. MYO5B mutations were associated with disrupted epithelial cell polarity implicating MYO5B in the regulation of intracellular protein trafficking [Muller et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies identified mutations in the MYO5B gene as a cause of most cases of MVID. 6,10,12 The loss of the MYO5B gene expression leads to defective cellular traffic and disrupted cell polarity of enterocytes. 6,10,18 Mutation in the syntaxin3 gene has been described recently in a case of variant form of MVID, presenting with milder clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,12 The loss of the MYO5B gene expression leads to defective cellular traffic and disrupted cell polarity of enterocytes. 6,10,18 Mutation in the syntaxin3 gene has been described recently in a case of variant form of MVID, presenting with milder clinical symptoms. 19 We also show expression of cell adhesion molecules beta-catenin and EpCAM as well as an ion pump Na/K ATPase to the basolateral membrane of normal enterocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation